Efficiency of steam reheating in heat recovery steam generator at thermal power plant with gas turbine topping - Romashova O. Yu. Olga Yurievna; Minor A. Aleksandr; Martyshev V. N. Vladimir Nikolaevich; Tubolev A. A. Aleksandr Anatolievich; Katalevskaya A. V. Aleksandra Vladimirovna (2017, 2017)
Title screen